Geological map of the Dominion of Canada and Newfoundland - Geological Survey of Canada (Producer)
Geological map of the Dominion of Canada and Newfoundland as of 1913. Legend on the right side is colour-coded to denote geological periods, epochs, acidic and basic rocks. Cities, towns, and bodies of water are named. International and provincial borders are outlined. Railroads and ferry/steamship routes can be seen throughout. Note in on the bottom right reads "Geographical base from engraved plates of the Department of the Interior. Geology of Newfoundland from official map of the colony. Geology compiled by G. A. Young. Scale is 1:6,336,000. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .